A novel plate settler in immersed membrane bioreactor (iMBR) in reducing membrane fouling - Wasu Rattananurak (2018)
© 2014 Balaban Desalination Publications. All rights reserved. Abstract: Membrane separation technology has been widely applied in water and wastewater treatments, especially in the water reclamation and recycling. However, the membrane fouling decreases the membrane efficiency and increases the cost of the process, thus limiting the membrane application. There are two types of membrane bioreactors (MBRs), immersed (iMBR) and side streamed. However, the membrane surfaces of these two types of MBR are always directly exposed to high concentration of suspended solids (SS) and easily get fouling. A novel MBR was designed to reduce membrane fouling. Incorporation of inclined plate in MBR can separate high SS from direct contact with the membrane surface and decreases membrane fouling. The iMBR used in this study consists of an aeration zone, a settling zone, and a filtration zone. The reactor operated under the upflow mode of operation with 0.06 μm membrane pore size and with and without membrane backwashing. The results showed that the novel iMBR can reduce the SS concentration in the filtration zone up to 97.3% and increase the permeate flux over 41.9% than that of normal iMBR.